OBJECT DETECTOR PROTOTYPE USING ULTRASONIC SENSOR FOR INDOOR SECURITY MONITORING SYSTEM - Satoro Disney Karwur; Hesky S. Kolibu; Verna A. Suoth (Sam Ratulangi University, 2014)
ABSTRACT A research has been conducted to make an object detector prototype using ultrasonic sensor for indoor security monitoring system. The testing object placed in front of the sensor and the measurement conducted in distance and angle variations. For indoor implementation, graphical display of object detection on computer screen given by blue-to-yellow transition to indicate the nearing object and its reverse to indicate the fading object. The trend of accuracy of the object distance measurement has a declining linear pattern, it means that the accuracy of object detection will decrease if the distance and or angle from the object to the detector are increase. Keywords: object detector, ultrasonic sensor,Â indoor security monitoring Â PURWARUPA DETEKTOR OBJEK MENGGUNAKAN SENSOR ULTRASONIK UNTUK SISTEM PEMANTAUAN KEAMANAN DALAM RUANGAN ABSTRAK Sebuah penelitian telah dilakukan untuk membuat purwarupa detektor objek menggunakan sensor ultrasonik untuk sistem pemantauan keamanan dalam ruangan. Objek pengujian diletakkan di depan sensor dan pengukuran dilakukan pada variasi jarak dan sudut.Â Untuk implementasi dalam ruangan, tampilan grafis pendeteksian objek pada layar komputer diberikan oleh transisi warna biru ke kuning untuk menunjukkan objek yang mendekat dan kebalikannya untuk menunjukkan objek yang menjauh. Tren akurasi pendeteksian objek memiliki pola menurun secara linear, itu berarti bahwa akurasi pendeteksian objek akan berkurang jika jarak dan atau sudut dari objek ke detektor bertambah besar. Kata kunci: detektor objek, sensor ultrasonik, pemantauan keamanan dalam ruangan